REDUCTION OF MAGNESIUM ON A BISMUTH SUBSTRATE IN DIMETHYLFORMAMIDE SOLUTION - Abildina A.K,; Agimbayeva A.M,; Urazkeldiyeva D.A, (Academic Journal of Physical and Chemical Sciences, 2019)
A modified anode material was obtained by reducing magnesium on the surface of a bismuth electrode in an anhydrous Mg(ClO4)2/dimethylformamide (DMF) system. The structure and composition of the obtained anode material were determined using a scanning electron microscope and X-ray spectral microanalysis. Analysis of the polarization curves revealed the electrochemical properties and the process of reversibility of the previously unexplored intermetallic compound consisting of Mg- Bi in Mg(ClO4)2/DMF system. Cyclic voltammograms showed that the processes in the system are quasi-reversible. It is proved that the process of electronic exchange is carried out by diffusion.